1995
DOI: 10.21273/jashs.120.5.771
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Sulfur Fertilization Influences Aromatic Flavor Components in Shrunken2 Sweet Corn Kernels

Abstract: Dimethyl sulfide (DMS) has been identified as the compound responsible for the characteristic aroma of cooked sweet corn (Zea mays L.) and, along with sugar and water-soluble polysaccharides, is one of the main flavor components in the kernels. Because of the close relationship between DMS and its amino acid precursor S-methylmethionine, the premise was formulated that it might be possible to improve sweet corn aroma and overall eating quality through enhanced production of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…Since, the increments of the mineral NPK fertilizers levels were associated with corresponding increases in all studied yield and its components characters. Such results were in general agreement with the findings of many researchers such as Yodpetch and Bautista (1984) for ear weight; Wong et al (1995) for ear weight, ear length, and kernels yield; and Oikeh et al (1997). These investigators reported that increasing the mineral fertilizers levels reflected significant increases on yield and its components.…”
Section: Yield and Yield Componentssupporting
confidence: 92%
See 2 more Smart Citations
“…Since, the increments of the mineral NPK fertilizers levels were associated with corresponding increases in all studied yield and its components characters. Such results were in general agreement with the findings of many researchers such as Yodpetch and Bautista (1984) for ear weight; Wong et al (1995) for ear weight, ear length, and kernels yield; and Oikeh et al (1997). These investigators reported that increasing the mineral fertilizers levels reflected significant increases on yield and its components.…”
Section: Yield and Yield Componentssupporting
confidence: 92%
“…Such results indicated generally that the used two sweet corn cultivars reflected high responses to the fertilization by using mineral NPK fertilizes. These results seemed to agree with the findings of Wong et al (1995) for ear weight, kernels yield, ear length of sweet corn; and Oikeh et al (1997) for grain yield and kernels yield of maize.…”
Section: Yield and Yield Componentssupporting
confidence: 91%
See 1 more Smart Citation
“…15 Increases in N fertility have been reported to influence sweet corn flavour by increasing concentrations of dimethyl sulphide. 16 In onion, N-form was reported to influence overall flavour intensity. 17 Alternatively, Randle 15 showed that high N levels changed the ratios of the flavour precursors such that MCSO accumulated at elevated levels that did not represent flavour quality from a typical fieldgrown onion.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, including recent work from this laboratory, have reported significant differences in kernel DMS levels among sweet corn hybrids (Dignan and Wiley 1976;Wong et al 1994). It was also recently reported that the concentration of kernel DMS could be increased by the application of nitrogen (N) and sulfur ( S ) fertilizer to the crop in the field (Wong et al 1993).…”
Section: Introductionmentioning
confidence: 98%